HUBUNGAN SELF EFFICACY DENGAN MOTIVASI SISWA DALAM BERWIRAUSAHA BERBASIS BIOLOGI - Ernawati, E; Heryanti, Erna; Mentari, Nurul Try (Biosfer: Jurnal Pendidikan Biologi, 2017)
Entrepreneurship is required to create a human resources quality in managing natural resources wisely and have the independence. The entrepreneurial spirit supported by self efficacy and motivation used to encourage students in entrepreneurship. Entrepreneurship can be honed and formed through education. This study aims to determine the correlation between self efficacy with students motivation in bioentrepreneurship . The study was conducted in SMA Negeri 98 Jakarta on April until May 2016. The reseach method used is survey, the correlation technique with a sample size of 125 students were taken by simple random sampling. Data collection techniques used questionnaire self efficacy of student in bioentrepreneurship and questionnaire motivation of student in bioentrepreneurship. The data of self efficacy and motivation of students in bioentrepreneurship is normal distribution and homogeneous. The results from this study show that there is a significant positive relation between self efficacy and students motivation in bioentrepreneurship with a correlation coefficient amounted to 0,725. Self efficacy contribute 52,5% for students motivation in bioentrepreneurship.